PROPOSAL OF A NEW METHOO OF ECOLOGICAL EVALUATION OF VEGETATION: THE CASE STUDY OF THE VEGETATION OF THE VENICE LAGOON LANDSCAPE ANO OF ITS SALT MARSHES - IGEGNOLI, V.; GIGLIO, E. (Annali di Botanica, 2004)
In frequent case studies, the heterogeneity of vegetation formation is very high, because of the frequency of both natural and human disturbances. Consequently, the phytosociological approach .and the auto-ecological one are not completely adequate for the evaluation or the ecological state of this vegetation in a landscape. So, this evaluation needs the integration with a landscape ecological method of vegetation survey through schedules, as indicated by Ingegnoli (2002). Each type of schedule has been designed to check the organisation level and to estimate the metastability of a tessera of a certain type of vegetation, considering both general ecological and landscape ecological characters: (A) Landscape e1ement characters (e.g. tessera, corridor), (8) Plant, biomass above ground, (C) Ecocoenotope pararneters. (D) Relation among the elements and their landscape parameters. There are four evaluation classes, the weights per class depending on an evaluation model designed as shown later on. The principal aim of this research is to design a new schedule, available for the main coenosis of salt marshes vegetation, which allows to complete a preliminary study on the Venice lagoon landscape dynamics, based on its vegetation. The landscape of the Venice lagoon is very complex and articulated, its main vegetation formations are the following: Underwater, Salt marshes. Littoral. Reclamation colonisations, Wet areas. Wooded patches and corridors. Agricultural cultivations, Urban green. The most important typc of vegetation is represented by salt marshes prairies called "barene", especially by Limonietum venetum (Pignani. 1966), This association can be divided into three sub-associations, the first with three facies: but the reality presents a large quantity of tesserae in intermediate or ecotonal states, even mixed with other associations (e,g, Spartinetum maritimae). The design and control of the schedule, the first measure of the community plant biomasses are a part of this study, me results of which will be discussed in this work.